2009
DOI: 10.1097/meg.0b013e32830ce7a7
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of magnetic resonance enterography and video capsule endoscopy in evaluating small bowel disease

Abstract: VCE can readily depict and characterize subtle mucosal lesions missed at MRE, whereas MRE yields additional mural, perienteric, and extraenteric information. Thus, VCE and MRE appear to be complementary methods which, when used in conjunction, may better characterize suspected small bowel disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 20 publications
0
20
0
1
Order By: Relevance
“…CE does appear to be superior to MRE for the evaluation of GI bleeding (mainly in non-IBD patients) 39 and superior for the detection of mucosal lesions in small studies specific to patients with CD. 40,41 The prospective studies comparing CE with both CTE and MRE are summarized in Table 2.…”
Section: Comparisons With Ct/mrementioning
confidence: 99%
“…CE does appear to be superior to MRE for the evaluation of GI bleeding (mainly in non-IBD patients) 39 and superior for the detection of mucosal lesions in small studies specific to patients with CD. 40,41 The prospective studies comparing CE with both CTE and MRE are summarized in Table 2.…”
Section: Comparisons With Ct/mrementioning
confidence: 99%
“…Furthermore, capsule endoscopy had a 71% diagnostic yield for active Crohn’s disease, compared with 39% for CT enterography/enteroclysis (p < 0.0001). Four trials compared capsule endoscopy with MR enterography in patients with established Crohn’s disease [11,12,13,14]. Diagnostic yields for capsule endoscopy and MR enterography were 70 and 79% (p = 0.65), respectively, but it is not clear how this correlated with either symptoms or the outcome of therapeutic intervention.…”
Section: Established Crohn’s Diseasementioning
confidence: 99%
“…Several meta-analyses 9 10 23 24 showed that CE has superior diagnostic yields to SB barium studies, ileocolonoscopy, push enteroscopy and CTE in both suspected and established SB CD. CE appears to be better than MRE at identifying SB mucosal lesions, while MRE is more accurate at diagnosing mural, peri-mural and extra-enteric manifestations 25 26. …”
Section: Discussionmentioning
confidence: 89%